Battery pack electrode

By using solid electrolytes of sulfur-converted electroactive materials and sulfur oxides in lithium-ion electrochemical batteries, combined with limited solvation liquid electrolytes and porous polymer spacers, the challenges of existing batteries in battery impedance, active material utilization and cathode ion transport are solved, and more efficient battery performance is achieved.

CN119920819APending Publication Date: 2025-05-02GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311439956.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Electrodes of existing lithium-ion electrochemical cells have challenges in achieving lower cell impedance, increased utilization of active materials, and increased cathode ion transport and kinetics.

Method used

An electrode containing a solid electrolyte that converts sulfur to electroactive materials and sulfur oxides is used to form a highly efficient electrochemical cell.

Benefits of technology

Through this technical means, electrochemical cells achieve lower battery impedance, improved utilization of active materials and enhanced cathode ion transport and dynamics, improving the overall performance of the cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920819A_ABST
    Figure CN119920819A_ABST
Patent Text Reader

Abstract

The present invention provides an electrochemical cell comprising an electrode comprising a sulfur converting electroactive material and a solid electrolyte comprising a sulfur oxide; a liquid electrolyte; a spacer; and a negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to electrodes, such as sulfur-containing electrodes, for lithium-ion electrochemical cells and methods of forming the same. Background Art

[0002] The present disclosure relates to electrodes, such as sulfur-containing electrodes, for lithium-ion electrochemical cells and methods of forming the same.

[0003] Advanced energy storage devices and systems are needed to meet the energy and / or power requirements of a variety of products, including automotive products, such as start-stop systems (e.g., 12 volt (V) start-stop systems), battery auxiliary systems, hybrid electric vehicles ("HEV"), and electric vehicles ("EV"). Typical lithium-ion and lithium-sulfur battery packs include at least two electrodes and an electrolyte and / or separator. One of the two electrodes acts as a positive electrode or cathode, while the other electrode acts as a negative electrode or anode. Each electrode is connected to a current collector (typically a metal, such as copper for the anode and aluminum for the cathode). A separator and / or electrolyte may be disposed between the negative electrode and the positive electrode. The electrolyte is suitable for conducting lithium ions between the electrodes and, like the two electrodes, may be in solid and / or liquid form and / or a mixture thereof in various cases. In the case of a solid-state battery pack comprising solid electrodes and a solid electrolyte, the solid electrolyte may physically separate the electrodes so that a separate separator is not required.

[0004] Lithium-sulfur batteries may include a cathode having a sulfur-based electroactive material, such as elemental sulfur (S) and / or Li2S x , where 1≤x≤8. Such cathodes typically include one or more layers of electroactive material, including, for example, a plurality of electroactive material particles disposed on or near one or more surfaces of a current collector.

[0005] For electrochemical cells that can address these challenges, it would be desirable to develop cathodes and methods of fabricating them that achieve lower cell impedance, increased active material utilization, and increased cathode ion transport and kinetics, e.g., methods and materials that can be readily integrated into common manufacturing processes. Summary of the Invention

[0006] In one exemplary embodiment, the present disclosure provides an electrochemical cell. The electrochemical cell may include an electrode comprising a sulfur-converting electroactive material and a solid electrolyte comprising a sulfur oxide; a liquid electrolyte; a separator; and a negative electrode.

[0007] In addition to one or more features described herein, the solid electrolyte may include 75Li2S-20P2S5-5P2O5; the liquid electrolyte may include bis(trifluoromethanesulfonyl)imide lithium salt and triethylene glycol dimethyl ether (G3) (Li(G3)TFSI), or bis(trifluoromethanesulfonyl)imide lithium salt and tetraethylene glycol dimethyl ether (G4) (Li(G4)TFSI), wherein the molar ratio of salt to solvent is 1:0.8.

[0008] In another exemplary embodiment, the liquid electrolyte may include a limited solvation liquid electrolyte.

[0009] In yet another exemplary embodiment, the separator may comprise a porous polymer separator.

[0010] In yet another exemplary embodiment, the sulfur-converting electroactive material may include S, S8, Li2S8, Li2S6, Li2S4, Li2S2, Li2S, Fe2S, or combinations thereof.

[0011] In yet another exemplary embodiment, the solid-state electrolyte may include yLi2S·(100-yx)P2S5·xP2O5, wherein y is 70 mol% to 80 mol% and x is 0.5 mol% to 10 mol%.

[0012] In yet another exemplary embodiment, the solid electrolyte may include Li 10 MP2S 12 , where M is Si, Ge or Sn; Li6PS5Cl; Li 3.25 Ge 0.25 P 0.75 S4; Li4GeS4; Li2S-P2S5 system; Li2S-SnS2 system; Li2S-SiS2 system; Li2S-GeS2 system; Li2S-B2S3 system; Li2S-Ga2S3 system; Li2S-P2S3 system; Li2S-Al2S3 system; Li 3.4 Si 0.4 P 0.6 S4; Li 10 GeP2S 11.7 O 0.3; Lithium argyrodite (argyrodite) Li6PS5X, wherein X is Cl, Br or I; Li2O-Li2S-P2S5 system; Li2S-P2S5-P2O5 system; Li2S-P2S5-GeS2 system; Li2S-P2S5-LiX system, wherein X is F, Cl, Br or I; Li2S-As2S5-SnS2 system; Li2S-P2S5-Al2S3 system; Li2S-LiX-SiS2 system, wherein X is or F, Cl, Br and I; 0.4LiI·0.6Li4SnS4; Li 11 Si2PS 12 ;Li2O-Li2S-P2S5-P2O5 system; Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0..3 ;Li 9.6 P3S 12 ;Li7P3S 11 ;Li9P3S9O3;Li 10.35 Ge 1.35 P 1.65 S 12 ;Li 10.35 Si 1.35 P 1.65 S 12 ;Li 9.81 Sn 0.81 P 2.1.9 S 12 ;Li 10 (Si 0.5 Ge 0.5 )P2S 12 ;Li 10 (Ge 0.5 Sne 0.5 )P2S 12 ;Li 10 (Si 0.5 Sn 0.5 )P2S 12 ;Li7P 2.9 Mn 0.1 S 10.7 I 0.3 ;Li 3.833 Sn 0.833 As 0.166 S4; LiI-Li4SnS4; Li4SnS4; Li 10.35 [Sn 0.27 Si 1.08 ]P 1.65 S 12 ; or a combination thereof.

[0013] In yet another exemplary embodiment, the liquid electrolyte may include a solvated ionic liquid including a lithium salt of bis(trifluoromethanesulfonyl)imide and diglyme (G2) (Li(G2)TFSI), a lithium salt of bis(trifluoromethanesulfonyl)imide and triglyme (G3) (Li(G3)TFSI), a lithium salt of bis(trifluoromethanesulfonyl)imide and tetraglyme (G4) (Li(G4)TFSI), a lithium salt of bis(fluorosulfonyl)imide and diglyme (G2) (Li(G2)FSI), a lithium salt of bis(fluorosulfonyl)imide and triglyme (G3) (Li(G3)FSI), a lithium salt of bis(fluorosulfonyl)imide and tetraglyme (G4) (Li(G4)TFSI). [Li(G4)]BETI), bis(pentafluoroethanesulfonyl)imide lithium salt and diglyme (G2) ([Li(G2)]BETI), bis(pentafluoroethanesulfonyl)imide lithium salt and triglyme (G3) ([Li(G3)]BETI), bis(pentafluoroethanesulfonyl)imide lithium salt and tetraglyme (G4) ([Li(G4)]BETI), cyano(trifluoromethanesulfonyl)imide lithium salt and diglyme (G2) ([Li(G2)]CTFSI), cyano(trifluoromethanesulfonyl)imide lithium salt and triglyme (G3) ([Li(G3)]CTFSI), cyano(trifluoromethanesulfonyl)imide lithium salt and tetraglyme (G4) ([Li(G4)] CTFSI), lithium perchlorate and diglyme (G2) ([Li(G2)]ClO4), lithium perchlorate and triglyme (G3) ([Li(G3)]ClO4), lithium perchlorate and tetraglyme (G4) ([Li(G4)]ClO4), lithium tetrafluoroborate and diglyme (G2) ([Li(G2)]BF4), lithium tetrafluoroborate and triglyme (G3) ([Li(G3)]BF4), lithium tetrafluoroborate and tetraglyme (G4) ([Li(G4)]BF4), lithium nitrate and diglyme (G2) ([Li(G2)]NO3), lithium nitrate and triglyme (G3) ([Li(G3)]NO3), lithium nitrate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]NO3), lithium trifluoromethanesulfonate and diethylene glycol dimethyl ether (G2) ([Li(G2)]OTf), lithium trifluoromethanesulfonate and triethylene glycol dimethyl ether (G3) ([Li(G3)]OTf), lithium trifluoromethanesulfonate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]OTf), lithium trifluoroacetate and diethylene glycol dimethyl ether (G2) ([Li(G2)]TFA), lithium trifluoroacetate and triethylene glycol dimethyl ether (G3) ([Li(G3)]TFA), lithium trifluoroacetate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]TFA), or a combination thereof.

[0014] In another exemplary embodiment, the liquid electrolyte may include an ionic liquid electrolyte including 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIM-TFSI), N-propyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR13TFSI), 1-butyl-1-methylpyrrolidone The present invention also provides the following: 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMIM-FSI), 1-butyl-3-methylimidazolium bis(fluorosulfonyl)imide (BMIM-FSI), N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR13-FSI), 1-butyl-1-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR14-FSI), or a combination thereof.

[0015] In another exemplary embodiment, the liquid electrolyte may include an organic solvent and a lithium salt, wherein the organic solvent includes ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, methyl propionate, γ-butyrolactone, γ-valerolactone, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoroethyl) carbonate (ETFE C), bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, methyl 3,3,3-trifluoropropionate or ethyl trifluoroacetate, tris(2,2,2-trifluoroethyl) orthoformate (TFEO), bis(2,2,2-trifluoroethyl) carbonate (BTC), 2,2,2-trifluoroethyl methyl carbonate (FEMC), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, ethoxymethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1 , 3-dioxolane (DOL), cyclopentane, diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), tetraethylene glycol dimethyl ether (G4) or a combination thereof; the lithium salt includes lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiBF2(C2O4))(LiODFB), lithium tetraphenylborate (LiB(C6H5) 4), lithium bis(oxalato)borate (LiB(C2O4)2) (LiBOB), lithium tetrafluorooxalatophosphate (LiPF4(C2O4)) (LiFOP), lithium nitrate (LiNO3), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonimide) (LiTFSI) (LiN(CF3SO2)2), lithium fluorosulfonimide (LiN(FSO2)2) (LiFSI), lithium fluoroalkyl phosphate (LiFAP) (Li3O4P), or a combination thereof.

[0016] In yet another exemplary embodiment, the sulfur-converting electroactive material may include a sulfur-carbon composite, a Li2S-C composite, sulfurized polyacrylonitrile, or a combination thereof.

[0017] In yet another exemplary embodiment, the electrode may further comprise a conductive material comprising carbon black, graphite, acetylene black, carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powder, liquid metal, conductive polymers, or combinations thereof.

[0018] In another exemplary embodiment, the electrode may further include a binder comprising styrene-butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), polytetrafluoroethylene (PTFE), poly(tetrafluoroethylene-co-perfluoro(3-oxa-4-pentenesulfonic acid)) lithium salt, sodium carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, ethylene propylene diene monomer (EPDM), or a combination thereof.

[0019] In yet another exemplary embodiment, the electrode may include 40 to 70 wt% of the sulfur-converting electroactive material; 5 to 30 wt% of the solid electrolyte; 0.1 to 20 wt% of the binder; and 0.1 to 30 wt% of the conductive material, based on the total weight of the electrode.

[0020] In yet another exemplary embodiment, the negative electrode may include lithium, graphite, graphene, hard carbon, soft carbon, carbon nanotubes, silicon, a silicon-containing alloy, a tin-containing alloy, or a combination thereof.

[0021] In one exemplary embodiment, the present disclosure provides an electrochemical cell. The electrochemical cell may include an electrode comprising a sulfur-converting electroactive material and an oxide solid electrolyte; a liquid electrolyte; a separator; and a negative electrode.

[0022] In addition to one or more features described herein, the liquid electrolyte may include a limited solvation liquid electrolyte including a solvated ionic liquid.

[0023] In another exemplary embodiment, the oxide solid state electrolyte may include Li 1+x Al x Ge 2-x (PO4)3(LAGP)(where 0≤x≤2), Li7La3Zr2O 12 (LLZO), or Li 1+x Al x Ti 2-x (PO4)3(LATP) (where 0≤x≤2); and the liquid electrolyte may include a lithium bis(trifluoromethanesulfonyl)imide salt and triethylene glycol dimethyl ether (G3) (Li(G3)TFSI), or a lithium bis(trifluoromethanesulfonyl)imide salt and tetraethylene glycol dimethyl ether (G4) (Li(G4)TFSI), wherein the molar ratio of the salt to the solvent is 1:0.8.

[0024] In one exemplary embodiment, the present disclosure provides an electrochemical cell. The electrochemical cell may include an electrode comprising a sulfur-converting electroactive material and a solid electrolyte comprising a sulfide; a liquid electrolyte; a separator; and a negative electrode.

[0025] In addition to one or more features described herein, the liquid electrolyte may include a limited solvation liquid electrolyte including a solvated ionic liquid.

[0026] The present invention discloses the following solutions:

[0027] Solution 1. An electrochemical cell comprising:

[0028] An electrode comprising:

[0029] Sulfur conversion electroactive materials, and

[0030] a solid electrolyte comprising a sulfur oxide;

[0031] Liquid electrolytes;

[0032] spacers; and

[0033] Negative electrode.

[0034] Option 2. The electrochemical cell according to Option 1, wherein:

[0035] The solid electrolyte comprises 75Li2S-20P2S5-5P2O5; and

[0036] The liquid electrolyte comprises

[0037] Lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether (G3) (Li(G3)TFSI), or

[0038] Lithium bis(trifluoromethanesulfonyl)imide and tetraethylene glycol dimethyl ether (G4) (Li(G4)TFSI), wherein the molar ratio of salt to solvent is 1:0.8.

[0039] Option 3. The electrochemical cell of Option 1, wherein the liquid electrolyte comprises a limited solvation liquid electrolyte.

[0040] Option 4. The electrochemical cell of Option 3, wherein the separator comprises a porous polymer separator.

[0041] Option 5. An electrochemical cell according to Option 1, wherein the sulfur-conversion electroactive material comprises S, S8, Li2S8, Li2S6, Li2S4, Li2S2, Li2S, Fe2S, or a combination thereof.

[0042] Option 6. An electrochemical cell according to Option 1, wherein the solid-state electrolyte comprises yLi2S·(100-yx)P2S5·xP2O5, wherein y is 70 mol% to 80 mol%, and x is 0.5 mol% to 10 mol%.

[0043] Option 7. The electrochemical cell according to Option 1, wherein the solid electrolyte comprises Li 10 MP2S 12 , where M is Si, Ge or Sn; Li6PS5Cl; Li 3.25 Ge 0.25 P 0.75 S4; Li4GeS4; Li2S-P2S5 system; Li2S-SnS2 system; Li2S-SiS2 system; Li2S-GeS2 system; Li2S-B2S3 system; Li2S-Ga2S3 system; Li2S-P2S3 system; Li2S-Al2S3 system; Li 3.4 Si 0.4 P 0.6 S4; Li 10 GeP2S 11.7 O 0.3 Lithium argyrodite Li6PS5X, wherein X is Cl, Br or I; Li2O-Li2S-P2S5 system; Li2S-P2S5-P2O5 system; Li2S-P2S5-GeS2 system; Li2S-P2S5-LiX system, wherein X is F, Cl, Br or I; Li2S-As2S5-SnS2 system; Li2S-P2S5-Al2S3 system; Li2S-LiX-SiS2 system, wherein X is or F, Cl, Br and I; 0.4LiI·0.6Li4SnS4; Li 11 Si2PS 12 ;Li2O-Li2S-P2S5-P2O5 system; Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0..3 ;Li 9.6 P3S 12 ;Li7P3S 11 ;Li9P3S9O3;Li 10.35 Ge 1.35 P 1.65 S 12 ;Li 10.35 Si 1.35 P 1.65 S 12 ;Li 9.81 Sn 0.81 P 2.1.9 S12 ; Li 10 (Si 0.5 Ge 0.5 )P2S 12 ; Li 10 (Ge 0.5 Sne 0.5 )P2S 12 ; Li 10 (Si 0.5 Sn 0.5 )P2S 12 ; Li7P 2.9 Mn 0.1 S 10.7 I 0.3 ; Li 3.833 Sn 0.833 As 0.166 S4; LiI - Li4SnS4; Li4SnS4; Li 10.35 [Sn 0.27 Si 1.08 P 1.65 S 12 ; or a combination thereof.

[0044] Option 8. An electrochemical cell according to Option 1, wherein the liquid electrolyte comprises a solvated ionic liquid, the solvated ionic liquid comprising a lithium salt of bis(trifluoromethanesulfonyl)imide and diethylene glycol dimethyl ether (G2) (Li(G2)TFSI), a lithium salt of bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether (G3) (Li(G3)TFSI), a lithium salt of bis(trifluoromethanesulfonyl)imide and tetraethylene glycol dimethyl ether (G4) (Li(G4)TFSI), a lithium salt of bis(fluorosulfonyl)imide and diethylene glycol dimethyl ether (G2) (Li(G2)FSI), a lithium salt of bis(fluorosulfonyl)imide and triethylene glycol dimethyl ether (G3) (Li(G3)FSI), a lithium salt of bis(fluorosulfonyl)imide and tetraethylene glycol dimethyl ether (G4)(Li(G4)FSI), bis(pentafluoroethanesulfonyl)imide lithium salt and diglyme (G2)([Li(G2)]BETI), bis(pentafluoroethanesulfonyl)imide lithium salt and triglyme (G3)([Li(G3)]BETI), bis(pentafluoroethanesulfonyl)imide lithium salt and tetraglyme (G4)([Li(G4)]BETI), cyano(trifluoromethanesulfonyl)imide lithium salt and diglyme (G2)([Li(G2)]CTFSI), cyano(trifluoromethanesulfonyl)imide lithium salt and triglyme (G3)([Li(G3)]CTFSI), cyano(trifluoromethanesulfonyl)imide lithium salt and tetraglyme (G4)([Li( G4)]CTFSI), lithium perchlorate and diglyme (G2) ([Li(G2)]ClO4), lithium perchlorate and triglyme (G3) ([Li(G3)]ClO4), lithium perchlorate and tetraglyme (G4) ([Li(G4)]ClO4), lithium tetrafluoroborate and diglyme (G2) ([Li(G2)]BF4), lithium tetrafluoroborate and triglyme (G3) ([Li(G3)]BF4), lithium tetrafluoroborate and tetraglyme (G4) ([Li(G4)]BF4), lithium nitrate and diglyme (G2) ([Li(G2)]NO3), lithium nitrate and triglyme (G 3)([Li(G3)]NO3), lithium nitrate and tetraglyme (G4)([Li(G4)]NO3), lithium trifluoromethanesulfonate and diglyme (G2)([Li(G2)]OTf), lithium trifluoromethanesulfonate and triglyme (G3)([Li(G3)]OTf), lithium trifluoromethanesulfonate and tetraglyme (G4)([Li(G4)]OTf), lithium trifluoroacetate and diglyme (G2)([Li(G2)]TFA), lithium trifluoroacetate and triglyme (G3)([Li(G3)]TFA), lithium trifluoroacetate and tetraglyme (G4)([Li(G4)]TFA), or a combination thereof.

[0045] Scheme 9. An electrochemical cell according to Scheme 1, wherein the liquid electrolyte comprises an ionic liquid electrolyte, the ionic liquid electrolyte comprising 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIM-TFSI), N-propyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR13TFSI), 1-butyl-1-methyl The bis(fluorosulfonyl)imide may be 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR14TFSI), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMIM-FSI), 1-butyl-3-methylimidazolium bis(fluorosulfonyl)imide (BMIM-FSI), N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR13-FSI), 1-butyl-1-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR14-FSI), or a combination thereof.

[0046] 10. The electrochemical cell of claim 1 , wherein the liquid electrolyte comprises:

[0047] Organic solvents, including ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, methyl propionate, γ-butyrolactone, γ-valerolactone, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoroethyl) carbonate (ETFEC), bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,3,3,3-hexafluoropropyl- 2,2,2-trifluoroethyl ether, methyl 3,3,3-trifluoropropionate or ethyl trifluoroacetate, tris(2,2,2-trifluoroethyl) orthoformate (TFEO), bis(2,2,2-trifluoroethyl) carbonate (BTC), 2,2,2-trifluoroethyl methyl carbonate (FEMC), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, ethoxymethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane (DOL), sulfolane, diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), tetraethylene glycol dimethyl ether (G4), or a combination thereof; and

[0048] Lithium salts, including lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiBF2(C2O4))(LiODFB), lithium tetraphenylborate (LiB(C6H5)4), lithium bis(oxalato)borate (LiB(C2O4)2)(L iBOB), lithium tetrafluorooxalatophosphate (LiPF4(C2O4))(LiFOP), lithium nitrate (LiNO3), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonimide) (LiTFSI)(LiN(CF3SO2)2), lithium fluorosulfonimide (LiN(FSO2)2)(LiFSI), lithium fluoroalkyl phosphate (LiFAP)(Li3O4P), or a combination thereof.

[0049] Option 11. An electrochemical cell according to Option 1, wherein the sulfur-conversion electroactive material comprises a sulfur-carbon composite, a Li2S-C composite, a sulfurized polyacrylonitrile, or a combination thereof.

[0050] Option 12. An electrochemical cell according to Option 1, wherein the electrode further comprises a conductive material, the conductive material comprising carbon black, graphite, acetylene black, carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powder, liquid metal, conductive polymer or a combination thereof.

[0051] Option 13. An electrochemical cell according to Option 1, wherein the electrode further comprises a binder, the binder comprising styrene-butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), polytetrafluoroethylene (PTFE), poly(tetrafluoroethylene-co-perfluoro(3-oxa-4-pentenesulfonic acid)) lithium salt, sodium carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, ethylene propylene diene monomer (EPDM) or a combination thereof.

[0052] 14. The electrochemical cell of 13, wherein the electrode comprises, based on the total weight of the electrode:

[0053] 40 to 70 weight percent of said sulfur-converting electroactive material;

[0054] 5 to 30 wt% solid electrolyte;

[0055] 0.1 to 20 wt% of said binder; and

[0056] 0.1 to 30 wt% of the conductive material.

[0057] Option 15. An electrochemical cell according to Option 1, wherein the negative electrode comprises lithium, graphite, graphene, hard carbon, soft carbon, carbon nanotubes, silicon, a silicon-containing alloy, a tin-containing alloy, or a combination thereof.

[0058] 16. An electrochemical cell comprising:

[0059] An electrode comprising

[0060] Sulfur conversion electroactive materials, and

[0061] Oxide solid electrolyte;

[0062] Liquid electrolytes;

[0063] spacers; and

[0064] Negative electrode.

[0065] Option 17. An electrochemical cell according to Option 16, wherein the liquid electrolyte comprises a limited solvation liquid electrolyte, and the limited solvation liquid electrolyte comprises a solvated ionic liquid.

[0066] 18. The electrochemical cell of 16, wherein:

[0067] The oxide solid electrolyte comprises

[0068] Li 1+x Al x Ge 2-x (PO4)3(LAGP)(where 0≤x≤2),

[0069] Li7La3Zr2O 12 (LLZO), or

[0070] Li 1+x Al x Ti 2-x (PO4)3(LATP) (where 0≤x≤2); and

[0071] The liquid electrolyte comprises

[0072] Lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether (G3) (Li(G3)TFSI), or

[0073] Lithium bis(trifluoromethanesulfonyl)imide and tetraethylene glycol dimethyl ether (G4) (Li(G4)TFSI), wherein the molar ratio of salt to solvent is 1:0.8.

[0074] 19. An electrochemical cell comprising:

[0075] An electrode comprising

[0076] Sulfur conversion electroactive materials, and

[0077] a solid electrolyte comprising a sulfide;

[0078] Liquid electrolytes;

[0079] spacers; and

[0080] Negative electrode.

[0081] Option 20. An electrochemical cell according to Option 19, wherein the liquid electrolyte comprises a limited solvation liquid electrolyte, and the limited solvation liquid electrolyte comprises a solvated ionic liquid.

[0082] The above features and advantages and other features and advantages of the present disclosure are readily apparent from the following detailed description when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0083] Other features, advantages, and details appear, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:

[0084] Figure 1 schematically illustrates an exploded isometric view of a prismatic battery cell including an anode, electrolyte material, separator, and cathode according to the present disclosure;

[0085] Figure 2 schematically illustrates a cross-sectional side view of an embodiment of a cathode;

[0086] Figure 3 schematically illustrates elements of a method for forming a cathode of a battery cell;

[0087] Figure 4 is a graphical representation showing the electrochemical performance of Comparative Example 1; and

[0088] Figure 5 is a graphical representation showing the electrochemical performance of Example 1. DETAILED DESCRIPTION

[0089] The following description is merely exemplary in nature and is in no way intended to limit the present disclosure, its application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate like or corresponding parts and features.

[0090] According to exemplary embodiments, electrodes for batteries such as lithium-sulfur batteries and methods of forming and using the same are disclosed. Such batteries can be incorporated into energy storage devices, such as rechargeable lithium-ion batteries, which can be used in automotive transportation applications (e.g., motorcycles, boats, tractors, buses, mobile homes, campers, and tanks). However, the present technology can also be used in other electrochemical devices, including, as non-limiting examples, aerospace components, consumer products, devices, buildings (e.g., houses, offices, sheds, and warehouses), office equipment and furniture, and industrial equipment machinery, agricultural or farm equipment, or heavy machinery. The present disclosure provides a rechargeable lithium-ion battery that exhibits lower cell impedance, increased active material utilization, and increased cathode ion transport and kinetics.

[0091] Referring to the drawings, wherein like reference numerals correspond to like or similar components throughout the several views, Figure 1 An embodiment of a prismatic lithium-ion battery cell 10 is schematically illustrated, comprising an electrode pair 15 having a cathode 20, a separator 40, and an anode 30 arranged in a stack and sealed in a flexible pouch 60 containing an electrolyte material 62. In one embodiment of the battery cell, a reference electrode can be arranged between the anode and the cathode. A first positive battery cell tab 26 and a second negative battery cell tab 36 protrude from the flexible pouch 60. The terms "anode" and "negative electrode" are used interchangeably. The terms "cathode" and "positive electrode" are used interchangeably. A single electrode pair 15 is illustrated comprising a cathode 20, a separator 40, and an anode 30 arranged therein. It should be understood that, depending on the application of the battery cell 10, multiple electrode pairs 15 can be arranged and electrically connected in the flexible pouch 60.

[0092] Cathode 20 includes a sulfur-converting electroactive material 22 disposed on a cathode current collector 24 , and cathode current collector 24 may have a foil portion 25 extending from the sulfur-converting electroactive material 22 to form a second battery cell tab 26 .

[0093] Anode 30 includes a second electroactive material 32 disposed on an anode current collector 34. Anode current collector 34 may be a metal substrate having a foil portion 35 extending from second electroactive material 32 to form a first battery cell tab 36.

[0094] The cathode current collector 24 and the anode current collector 34 may be metal plate-shaped elements that contact the respective first electroactive material 22 and the second electroactive material 32 over a considerable interfacial surface area. The purpose of the cathode current collector 24 and the anode current collector 34 is to exchange free electrons with the respective first electroactive material 22 and the second electroactive material 32 during discharge and charge.

[0095] Cathode current collector 24 may be a metal substrate in the form of a planar sheet made of aluminum or an aluminum alloy and may have a thickness of, for example, 0.02 millimeters (mm). Separator 40 is disposed between cathode 20 and anode 30 to physically and electrically isolate anode 30 from cathode 20.

[0096] In one embodiment, the anode current collector 34 can be a flat, plate-shaped metal substrate in the form of a rectangular planar sheet. In one embodiment, the anode current collector 34 can be arranged as a planar sheet having a non-rectangular shape, a coil configuration, a cylindrical configuration, or another configuration.

[0097] Anode current collector 34 may be made of copper, a copper alloy, stainless steel, nickel, or the like, or another material that does not alloy with lithium. In one embodiment, anode current collector 34 may have a thickness of, for example, 0.02 mm. Second electroactive material 32 is present in a second electroactive material layer that may be applied to one or both surfaces of anode current collector 34.

[0098] The cathode current collector 24, the anode current collector 34, or a combination thereof may include stainless steel, aluminum, nickel, iron, titanium, copper, tin, a suitable conductive material, or a combination thereof. For example, the cathode current collector 24, the anode current collector 34, or a combination thereof may be a cladding foil, wherein one side of the current collector 24, 34 (e.g., the first side or the second side) includes a metal (e.g., a first metal), and the other side of the current collector 24, 34 (e.g., the other side of the first side or the second side) includes another metal (e.g., a second metal). The cladding foil may include, for example, aluminum-copper (AlCu), nickel-copper (NiCu), stainless steel-copper (SS-Cu), aluminum-nickel (Al-Ni), aluminum-stainless steel (Al-SS), and nickel stainless steel (Ni-SS). The cathode current collector 24, the anode current collector 34, or a combination thereof may be pre-coated, such as a graphene or carbon-coated aluminum current collector. The cathode current collector 24, the anode current collector 34, or a combination thereof may be in the form of a foil, a slit mesh, a woven mesh, or a combination thereof.

[0099] An electrolyte material 62 that conducts lithium ions may be contained within separator 40 and may be exposed to each of cathode 20 and anode 30 to allow lithium ions to move between cathode 20 and anode 30. Lithium ions may be stripped from anode 30 during discharge, or electrons may be released from cathode 20 during charge, with the electrons flowing through current collectors 34 and 24, respectively, through an external circuit connected to a load or charger, and then to the opposing current collectors (24 and 34) and electrodes (20 and 30), where they reduce the lithium ions as they are intercalated.

[0100] The cathode 20 and the anode 30 are each manufactured as an electrode material capable of depositing and stripping lithium ions (on the anode) or inserting and deinserting (on the cathode). The electrode materials of the cathode 20 and the anode 30 are formulated to store lithium at different electrochemical potentials relative to a common reference electrode (e.g., lithium). In the configuration of the electrode pair 15, the anode 30 stores deposited or plated lithium at a lower electrochemical potential (i.e., a higher energy state) than the cathode 20, so that when the anode 30 is lithiated, an electrochemical potential difference exists between the cathode 20 and the anode 30. The electrochemical potential difference of each battery cell 10 can result in a charging voltage of 3V to 5V and a nominal open circuit voltage of 2.9V to 4.2V, which can allow lithium ions to be reversibly transferred between the cathode 20 and the anode 30 spontaneously (discharge phase) or by applying an external voltage (charge phase) during the operating cycle. In one embodiment, the thickness of the anode 30 is 10μm to 20μm.

[0101] Disclosed are a positive electrode comprising a sulfur-converting electroactive material and a solid electrolyte, and an electrochemical cell comprising the electrode and a limited-solvation liquid electrolyte. The liquid electrolyte may be a limited-solvation liquid electrolyte, which may help prevent sulfur dissolution and catalyze sulfur reactions by including a solid electrolyte in the electrode.

[0102] As used herein, the phrase "converting an electroactive material" refers to the conversion of an electroactive material into a + The crystal structure of the cathode changes when the cathode absorbs Li. Bonds may break and new compounds may form. An example of such a material is Li2S. In contrast, the crystal structure of an intercalated electroactive material (also known as an intercalated electroactive material) changes when the electroactive material absorbs Li. + An example of such a material is nickel-cobalt-manganese (NCM).

[0103] As used herein, the phrase "limited solvation liquid electrolyte" refers to an electrolyte that does not dissolve the sulfur cathode. Examples of limited solvation liquid electrolytes are Li[G3]TFSI or Li[G4] 0.8 In contrast, a “highly solvating electrolyte” is one that can dissolve a sulfur cathode, such as 1 mole (mole per liter, M) LiTFSI in DME:DOL.

[0104] The first electroactive material layer 23 of the cathode 20 can include a sulfur-converting electroactive material 22, a solid electrolyte 28 including an oxide, a sulfide, or a sulfur oxide, and a first binder 29. Based on the total weight of the cathode, the cathode can include 30% to 70% by weight, such as 40% to 70% by weight, of the sulfur-converting electroactive material, 5% to 50% by weight, such as 5% to 30% by weight, of the solid electrolyte, 0.1% to 30% by weight, such as 0.1% to 20% by weight, of the first conductive material, and 0.1% to 20% by weight of the first binder.

[0105] The solid-state electrolyte of the disclosed electrode combines with the sulfur-converting electroactive material to form a fixed (e.g., "bound") or immovable portion of the solid structure of the cathode. The first binder can structurally reinforce the sulfur-converting electroactive material and the solid-state electrolyte. As further described herein, the electrolyte material that may be present within the pores of the cathode is not a static feature of the cathode. The electrode can have a porosity of 10% to 60%.

[0106] The cathode may be in the form of a layer having a thickness of 1 μm to 1,000 μm, for example, 5 μm to 400 μm or 10 μm to 300 μm. The cathode may be defined by a plurality of sulfur-converting electroactive materials, for example, including the sulfur-converting electroactive material. The average particle size of the sulfur-converting electroactive material may be 0.01 μm to 50 μm, for example, 1 μm to 20 μm.

[0107] The sulfur-converting electroactive material 22 may be, for example, S, S8, Li2S8, Li2S6, Li2S4, Li2S2, Li2S, Fe2S, or a combination thereof. The sulfur-converting electroactive material may include a sulfur-carbon composite (e.g., a sulfur-converting electroactive material supported on carbon), a Li2S-C composite, sulfurized polyacrylonitrile, or a combination thereof. The sulfur-converting electroactive material should fully undergo lithiation and delithiation while serving as the positive terminal of the battery cell.

[0108] The sulfur-converting electroactive material can be present in the cathode in an amount greater than or equal to 50 wt%, greater than or equal to 60 wt%, greater than or equal to 70 wt%, greater than or equal to 80 wt%, greater than or equal to 90 wt%, greater than or equal to 95 wt%, based on the total weight of the cathode; or in an amount from 50 wt% to 99 wt%, from 70 wt% to 99 wt%, or from 90 wt% to 99 wt%, based on the total weight of the cathode. The first electroactive material can include a sulfur-carbon composite, for example, in an amount from 50 wt% to 95 wt%, based on the total weight of the cathode, and the weight ratio of sulfur to carbon in the sulfur-carbon composite can be from 1:1 to 9:1.

[0109] The solid electrolyte 28 may include yLi2S·(100-yx)P2S5·xP2O5, wherein y is 70 mol% to 80 mol% and x is 0.5 mol% to 10 mol%. The solid electrolyte 28 may include Li 10 MP2S 12 , where M is Si, Ge or Sn; Li6PS5Cl; Li 3.25 Ge 0.25 P 0.75 S4; Li4GeS4; Li2S-P2S5 system; Li2S-SnS2 system; Li2S-SiS2 system; Li2S-GeS2 system; Li2S-B2S3 system; Li2S-Ga2S3 system; Li2S-P2S3 system; Li2S-Al2S3 system; Li 3.4 Si 0.4 P 0.6 S4; Li 10 GeP2S 11.7 O 0.3 Lithium argyrodite Li6PS5X, wherein X is Cl, Br or I; Li2O-Li2S-P2S5 system; Li2S-P2S5-P2O5 system; Li2S-P2S5-GeS2 system; Li2S-P2S5-LiX system, wherein X is F, Cl, Br or I; Li2S-As2S5-SnS2 system; Li2S-P2S5-Al2S3 system; Li2S-LiX-SiS2 system, wherein X is or F, Cl, Br and I; 0.4LiI·0.6Li4SnS4; Li 11 Si2PS 12 ;Li2O-Li2S-P2S5-P2O5 system; Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0..3 ;Li 9.6 P3S 12 ;Li7P3S 11 ;Li9P3S9O3;Li 10.35 Ge 1.35 P 1.65 S 12 ;Li 10.35 Si 1.35 P 1.65 S 12 ;Li 9.81 Sn 0.81 P 2.1.9 S 12 ;Li 10 (Si 0.5 Ge 0.5 )P2S12 ; Li 10 (Ge 0.5 Sne 0.5 )P2S 12 ; Li 10 (Si 0.5 Sn 0.5 )P2S 12 ; Li7P 2.9 Mn 0.1 S 10.7 I 0.3 ; Li 3.833 Sn 0.833 As 0.166 S4; LiI - Li4SnS4; Li4SnS4; Li 10.35 [Sn 0.27 Si 1.08 P 1.65 S 12 ; or a combination thereof.

[0110] The limited solvation liquid electrolyte may include a solvated ionic liquid, such as a lithium salt of bis(trifluoromethanesulfonyl)imide and diglyme (G2) (Li(G2)TFSI), a lithium salt of bis(trifluoromethanesulfonyl)imide and triglyme (G3) (Li(G3)TFSI), a lithium salt of bis(trifluoromethanesulfonyl)imide and tetraglyme (G4) (Li(G4)TFSI), a lithium salt of bis(fluorosulfonyl)imide and diglyme (G2) (Li(G2)FSI), a lithium salt of bis(fluorosulfonyl)imide and triglyme (G3) (Li(G3)FSI), a lithium salt of bis(fluorosulfonyl)imide and tetraglyme (G4) (Li(G4)FSI), a lithium salt of bis(trifluoromethane ...trifluoromethanesulfonyl)imide and triglyme (G3) (Li(G3)FSI), a lithium salt of bis(trifluorosulfonyl)imide and tetraglyme (G4) (Li(G4)FSI), a lithium salt of bis(trifluoromethanesulfonyl)imide and tetra Pentafluoroethanesulfonyl)imide lithium salt and diethylene glycol dimethyl ether (G2) ([Li(G2)]BETI), bis(pentafluoroethanesulfonyl)imide lithium salt and triethylene glycol dimethyl ether (G3) ([Li(G3)]BETI), bis(pentafluoroethanesulfonyl)imide lithium salt and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]BETI), cyano(trifluoromethanesulfonyl)imide lithium salt and diethylene glycol dimethyl ether (G2) ([Li(G2)]CTFSI), cyano(trifluoromethanesulfonyl)imide lithium salt and triethylene glycol dimethyl ether (G3) ([Li(G3)]CTFSI), cyano(trifluoromethanesulfonyl)imide lithium salt and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]CTFSI), high Lithium chlorate and diethylene glycol dimethyl ether (G2) ([Li(G2)]ClO4), lithium perchlorate and triethylene glycol dimethyl ether (G3) ([Li(G3)]ClO4), lithium perchlorate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]ClO4), lithium tetrafluoroborate and diethylene glycol dimethyl ether (G2) ([Li(G2)]BF4), lithium tetrafluoroborate and triethylene glycol dimethyl ether (G3) ([Li(G3)]BF4), lithium tetrafluoroborate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]BF4), lithium nitrate and diethylene glycol dimethyl ether (G2) ([Li(G2)]NO3), lithium nitrate and triethylene glycol dimethyl ether (G3) ([Li (G3)]NO3), lithium nitrate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]NO3), lithium trifluoromethanesulfonate and diethylene glycol dimethyl ether (G2) ([Li(G2)]OTf), lithium trifluoromethanesulfonate and triethylene glycol dimethyl ether (G3) ([Li(G3)]OTf), lithium trifluoromethanesulfonate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]OTf), lithium trifluoroacetate and diethylene glycol dimethyl ether (G2) ([Li(G2)]TFA), lithium trifluoroacetate and triethylene glycol dimethyl ether (G3) ([Li(G3)]TFA), lithium trifluoroacetate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]TFA), or a combination thereof.

[0111] The liquid electrolyte may include a lithium salt and an ionic liquid, wherein the ionic liquid includes 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIM-TFSI), N-propyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR13TFSI), 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMIM-FSI), 1-butyl-3-methylimidazolium bis(fluorosulfonyl)imide (BMIM-FSI), N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR13-FSI), 1-butyl-1-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR14-FSI), or a combination thereof.

[0112] The liquid electrolyte may include an organic solvent and a lithium salt, wherein the organic solvent includes ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, methyl propionate, γ-butyrolactone, γ-valerolactone, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoroethyl) carbonate (ETFEC), bis(2,2, 2-trifluoroethyl) ether (BTFE), 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, methyl 3,3,3-trifluoropropionate or ethyl trifluoroacetate, tris(2,2,2-trifluoroethyl) orthoformate (TFEO), bis(2,2,2-trifluoroethyl) carbonate (BTC), 2,2,2-trifluoroethyl methyl carbonate (FEMC), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, ethoxymethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane Cyclohexane (DOL), cyclopentane, diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), tetraethylene glycol dimethyl ether (G4) or a combination thereof; the lithium salt includes lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiBF2 (C2O4)) (LiODFB), lithium tetraphenylborate (LiB (C6H5) 4), Lithium bis(oxalato)borate (LiB(C2O4)2) (LiBOB), lithium tetrafluorooxalatophosphate (LiPF4(C2O4)) (LiFOP), lithium nitrate (LiNO3), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonimide) (LiTFSI) (LiN(CF3SO2)2), lithium fluorosulfonyl imide (LiN(FSO2)2) (LiFSI), lithium fluoroalkyl phosphate (LiFAP) (Li3O4P), or a combination thereof.

[0113] Cathode 20 can include a first conductive material. For example, sulfur-converting electroactive material 22 can be mixed with a first conductive material that provides an electron conduction path. The first conductive material can be present in cathode 20 in an amount of 1 wt % to 20 wt %, 1 wt % to 15 wt %, or 1 wt % to 10 wt %, based on the total weight of cathode 20. Inclusion of the disclosed solid-state electrolyte can reduce the amount of first conductive material that can otherwise be included in the cathode.

[0114] Examples of the first conductive material include carbon black (eg, Super P), graphite, acetylene black (eg, KETCHENTM Black or DENKA TM Black), carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powders (e.g., copper, nickel, steel, or iron), liquid metals (e.g., Ga, GaInSn), conductive polymers (e.g., including polyaniline, polythiophene, polyacetylene, polypyrrole, etc.), or combinations thereof. As used herein, the term "graphene nanosheet" refers to a stack of nanosheets or graphene layers. Such a first conductive material in particle form may have a circular geometry or an axial geometry.

[0115] The term "axial geometry" refers to particles that generally have a rod, fiber, or other cylindrical shape with a distinct long or elongated axis. The aspect ratio (AR) of a cylindrical shape (e.g., a fiber or rod) can be defined as AR=L / D, where L is the length of the longest axis and D is the diameter of the cylinder or fiber. Electroactive material particles suitable for use in the exemplary axial geometry of the present disclosure may have a high aspect ratio, for example, from 10 to 5,000. Sulfur-converting electroactive material particles having an axial geometry include fibers, wires, flakes, whiskers, filaments, tubes, rods, etc. The term "circular geometry" generally applies to particles with a lower aspect ratio, for example, an aspect ratio close to 1 (e.g., less than 10). It should be noted that the particle geometry can vary from a true circular shape and can, for example, include rectangular or elliptical shapes, including prolate spheroids or oblate spheroids, agglomerated particles, polygonal (e.g., hexagonal) particles, or other shapes generally having a low aspect ratio. Prolate spheroids can have a disk shape with a relatively high aspect ratio. Thus, particles of generally circular geometry are not limited to relatively low aspect ratio and spherical shapes.

[0116] The sulfur-converting electroactive material 22 can be mixed with a first binder 29 to improve the structural integrity of the cathode 20. The first binder 29 can be present in the cathode 20 in an amount of 1 wt % to 20 wt %, 1 wt % to 15 wt %, or 1 wt % to 10 wt %, based on the total weight of the cathode 20.

[0117] The binder may include styrene-butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), polytetrafluoroethylene (PTFE), poly(tetrafluoroethylene-co-perfluoro(3-oxa-4-pentenesulfonic acid)) lithium salt, sodium carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, ethylene propylene diene monomer rubber (EPDM) or a combination thereof.

[0118] Without wishing to be bound by any theory, it is believed that by including the disclosed solid-state electrolyte in a sulfur cathode, performance is improved by reducing cell impedance, increasing active material utilization by providing more reaction sites for sulfur redox reactions, and increasing cathode ion transport and kinetics. An electrochemical cell comprising a cathode comprising a sulfur-converting electroactive material and an electrolyte material comprising a solvated ionic liquid (e.g., a limited solvation electrolyte) can exhibit a desirable specific capacity, e.g., 1 to 5 milliampere-hours per square centimeter (mAh / cm 2 ). Solid-state electrolytes can help achieve improved kinetics and energy density.

[0119] An electrochemical cell comprising a cathode comprising a solid-state electrolyte and an electrolyte material comprising an organic solvent and a lithium salt (e.g., a highly solvated electrolyte) can exhibit desirable properties when the volume ratio of electrolyte to sulfur is reduced to less than 8: 1. Reducing the amount of such electrolyte can be desirable.

[0120] Figure 2 One embodiment of a cathode 20 is schematically illustrated, comprising a cathode current collector 24 having a first electroactive material layer 23 thereon after drying a sulfur-converting electroactive material slurry. In one embodiment and as shown, the first electroactive material layer 23 can be applied to one side of the cathode current collector 24. The first electroactive material layer 23 can be applied to both sides of the cathode current collector 24. The first electroactive material layer 23 can include 30% to 70% by weight, such as 40% to 70% by weight, of the sulfur-converting electroactive material 22; 5% to 50% by weight, such as 5% to 30% by weight, of a solid electrolyte; 0.1% to 20% by weight of a first binder; and 0.1% to 30% by weight of a first conductive material.

[0121] In one embodiment, the first electroactive material layer 23 may have a thickness of 30 μm to 300 μm. In one embodiment, the first electroactive material layer 23 may have a thickness of, for example, 35 μm to 150 μm.

[0122] The sulfur-converting electroactive material slurry includes a mixture of sulfur-converting electroactive material 22, solid electrolyte 28, first binder 29, optional first conductive material, and solvent. The sulfur-converting electroactive material 22 may have a maximum particle size of 100 μm and a minimum particle size of 100 nm.

[0123] The first binder 29 may serve as a binding material to combine the sulfur-converting electroactive material 22, the solid electrolyte 28, the optional conductive material, and the cathode current collector 24. The first binder 29 may be in the form of a powder, a resin, or dissolved in a solvent.

[0124] The mixture of the sulfur-converting electroactive material 22, the solid electrolyte 28, the first binder 29 forming the first electroactive material layer 23, and the optional first conductive material is mixed using an organic solvent or water to form a sulfur-converting electroactive material slurry, such as Figure 3 As shown in step S301 of the method 300, the first electroactive material layer 23 including the sulfur-converting electroactive material slurry can be applied (eg, cast) onto the cathode current collector 24, as shown in FIG. Figure 3 As shown in step S302 of the method 300 , and dried to form a cathode.

[0125] In one embodiment, the first electroactive material layer 23 can be applied to the cathode current collector 24 by gravure coating, slot die coating, or dip coating. Slot die coating is a deposition technique in which a slurry of sulfur-converting electroactive material 22 is delivered to the substrate of the cathode current collector 24 through a narrow slit positioned close to the surface. A major advantage of the slot die coating method is the simple relationship between the wet film coating thickness, the solution flow rate, and the speed of the coating substrate relative to the coating head. In addition, slot die coating is able to obtain extremely uniform films over large areas. Slot die coating is one of a variety of methods that can be used to deposit thin liquid films onto the surface of a substrate. One of the main advantages of slot die coating is that it can be easily integrated into scale-up processes (including roll-to-roll coating and sheet-to-sheet deposition systems).

[0126] In one embodiment, the first electroactive material layer 23 comprising a sulfur-converting electroactive material slurry may be applied to the cathode current collector 24 by immersing the cathode current collector 24 in a bath comprising the sulfur-converting electroactive material slurry.

[0127] The cathode current collector 24 having the first electroactive material layer 23 applied thereon is subjected to a drying process to bond the first electroactive material layer 23 to the surface of the cathode current collector 24, thereby forming the cathode 20. Figure 3 As shown in step S303 of method 300. The drying process may include subjecting the cathode current collector 24 having the applied first electroactive material layer 23 to a high temperature environment for a period of time to remove the solvent, which may include subjecting the cathode current collector 24 having the applied first electroactive material layer 23 to a material layer 23 calendaring process to improve the adhesion of the first electroactive material layer 23 to the surface of the cathode current collector 24. After the first electroactive material layer 23 is bonded to the surface of the cathode current collector 24, the cathode current collector 24 having the applied first electroactive material layer 23 is subjected to a temperature of 60°C to 150°C for a period of 1 to 60 minutes to dry and remove the solvent.

[0128] Thus, a wet process for forming a cathode may include mixing a sulfur-converted electroactive material, a disclosed solid-state electrolyte, and a first binder in a solvent to form a slurry; casting the slurry on a current collector; and drying the slurry to form an electrode including the disclosed solid-state electrolyte. The solvent may include toluene, an alkane, anisole, an organic phosphate, or a combination thereof.

[0129] The dry process for forming the cathode may include dry mixing a sulfur-converted electroactive material, the disclosed solid electrolyte, and a first binder to form a mixture; coating the mixture on a current collector to form a coated current collector; and calendering the coated current collector to form an electrode comprising the disclosed solid electrolyte. The mixing may include double-edged grinding, ball milling, using a mixer with cyclic mixing, or a combination thereof. Coating the mixture on the current collector may include dry coating, dry spraying, hot pressing and melt extrusion, three-dimensional printing, or a combination thereof. The calendering may include a pressure of 20 to 500 MPa.

[0130] The anode may be in the form of a layer having a thickness of 1 μm to 1,000 μm, for example 5 μm to 400 μm or 10 μm to 300 μm. The anode may be defined by, for example, including, a plurality of second electroactive materials. The second electroactive material may have an average particle size of 0.01 μm to 50 μm, for example 1 μm to 20 μm.

[0131] The electroactive material layer of the anode may include a second electroactive material, a second conductive material, and a second binder. Based on the total weight of the anode, the anode may contain 30% to 100% by weight of the second electroactive material, 0% to 30% by weight of the second conductive material, 0% to 20% by weight of the second binder, and 0% to 30% by weight of the electrolyte material.

[0132] The anode includes a second electroactive material as a lithium host material capable of serving as a negative terminal for a lithium-ion battery. For example, the anode may include a lithium host material (e.g., the second electroactive material) capable of serving as a negative terminal for a battery cell. The anode may be defined by a plurality of particles of the second electroactive material.

[0133] The anode may include a second electroactive material comprising lithium, for example, lithium metal, a lithium alloy (e.g., a lithium silicon alloy, a lithium aluminum alloy, a lithium indium alloy, a lithium tin alloy, or a combination thereof), or a combination thereof. The anode may also include silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, iron sulfide (FeS), Li4Ti5O 12 , or a combination thereof, for example, silicon mixed with graphite. The anode can be lithium metal itself. In a

[0134] The second electroactive material can be present in the anode in an amount of 70 to 100 weight percent, 70 to 98 weight percent, 70 to 95 weight percent, 80 to 95 weight percent, based on the total weight of the anode.

[0135] The anode may include a second conductive material. For example, the second electroactive material may be mixed with a second conductive material that provides an electron conduction path. The second conductive material may be present in the anode in an amount of 0% to 30% by weight, 1% to 25% by weight, 1% to 20% by weight, 1% to 10% by weight, 3% to 20% by weight, or 5% to 15% by weight, based on the total weight of the anode.

[0136] The second conductive material may be the same as or different from the first conductive material and may include, for example, carbon black (eg, SuperP), graphite, acetylene black (eg, KETCHEN TM Black or DENKA TM black), carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powders (e.g., copper, nickel, steel, or iron), liquid metals (e.g., Ga, GaInSn), conductive polymers (e.g., including polyaniline, polythiophene, polyacetylene, polypyrrole, etc.), or combinations thereof.

[0137] Anode can include a second adhesive. For example, the second electroactive material can be mixed with a second adhesive that improves the structural integrity of anode. The second adhesive can be present in anode in an amount of 0 wt % to 30 wt %, 1 wt % to 25 wt %, 1 wt % to 20 wt %, 1 wt % to 10 wt %, 3 wt % to 20 wt % or 5 wt % to 15 wt % based on the gross weight of anode. The second adhesive can include, for example, PTFE, sodium carboxymethylcellulose (CMC), styrene-butadiene rubber (SBR), poly (vinylidene fluoride) (PVDF), acrylonitrile-butadiene rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, ethylene propylene diene monomer (EPDM) or a combination thereof.

[0138] The separator can have a thickness that can be from 10 μm to 50 μm. The separator can include a porous polymer (e.g., a polyolefin) that provides thermal stability. A porous separator can be used with the disclosed sulfur-converting electroactive materials and a liquid electrolyte with limited solvation (e.g., an electrolyte that does not dissolve the sulfur cathode).

[0139] Examples of polyolefins include polyethylene (PE) (and variants such as high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-high molecular weight polyethylene (UHMWPE)), polypropylene (PP), and blends of PE and PP. The polymer can electrically insulate and physically separate the cathode and anode.

[0140] The separator can be a solid polymer electrolyte material that includes a polymer such as polyethylene oxide (PEO), polypropylene oxide (PPO), polyacrylonitrile (PAN), a solid electrolyte material (such as an oxide-based electrolyte material or a sulfide-based electrolyte material), or a gel polymer electrolyte material with a lithium salt or swollen with a lithium salt solution. During applicable discharge and charge cycles, the cathode and anode reversibly exchange lithium ions through the separator.

[0141] The separator may comprise, for example, a microporous polymer separator comprising a polyolefin or polytetrafluoroethylene (PTFE). The polyolefin may be a homopolymer (derived from a single monomer component) or a heteropolymer (derived from more than one monomer component), which may be linear or branched. If the heteropolymer is derived from two monomer components, the polyolefin may exhibit any copolymer chain arrangement, including those of block copolymers or random copolymers. Similarly, if the polyolefin is a heteropolymer derived from more than two monomer components, it may likewise be a block copolymer or a random copolymer. The polyolefin may be polyethylene (PE), polypropylene (PP), or a blend of PE and PP, or a multilayer porous membrane of PE, PP or a combination thereof, such as a PP-PE double layer structure or a PP-PE-PP three layer structure. Commercially available polyolefin porous separator membranes include those available from Celgard LLC. 2500 (single-layer polypropylene separator) and 2325 (three-layer polypropylene / polyethylene / polypropylene separator).

[0142] When the separator is a microporous polymer separator, it can be a single layer or a multilayer laminate, which can be manufactured by a dry or wet process. For example, in some cases, a single layer of polyolefin can form the entire separator. For example, the separator can be a fiber membrane with a large number of holes extending between the opposing surfaces, and can have an average thickness of less than one millimeter. Multiple discrete layers of similar or different polyolefins can be assembled to form a microporous polymer separator. The separator may include polymers other than polyolefins, such as polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polyamide, polyimide, poly(amide-imide) copolymer, polyetherimide, cellulose or a combination thereof, or any suitable material for producing the desired porous structure. The separator may include a cellulose separator, a PVDF membrane and a porous polyimide membrane.

[0143] The separator may include high-temperature stable polymers such as polyimide nanofiber-based nonwovens, nano-sized Al2O3 and poly(lithium 4-styrenesulfonate)-coated polyethylene films, SiO2-coated polyethylene, copolyimide-coated polyethylene, polyetherimide (PEI), bisphenol-acetone diphthalic anhydride (BPADA) and paraphenylenediamine, expanded polytetrafluoroethylene reinforced polyvinylidene fluoride-hexafluoropropylene, etc. The separator may be a high-temperature stable separator and include a sandwich structure of PVDF / poly(m-phenylene isophthalamide) (PMIA) / PVDF nanofiber separator.

[0144] The separator may include a ceramic coating, a heat-resistant material coating, or a combination thereof. The ceramic coating, the heat-resistant material coating, or a combination thereof may be provided on one or more sides of the separator. The material forming the ceramic coating may be aluminum oxide (Al2O3), silicon dioxide (SiO2), titanium dioxide (TiO2), or a combination thereof. The heat-resistant material may be, for example, Nomex, aramid, or a combination thereof. A polymer (e.g., a polyolefin) may be included in the separator as a fiber layer to help provide the separator with appropriate structural and porosity characteristics.

[0145] The separator can be infiltrated with a liquid electrolyte material throughout the pores of the polymer. The liquid electrolyte material that wets both the cathode and anode can include a lithium salt dissolved in a non-aqueous solvent. The liquid electrolyte material can wet the separator (e.g., filling 5% to 100%, such as 90%, of its porosity).

[0146] The cathode, anode, and separator can each include (e.g., within their pores) an electrolyte material capable of conducting lithium ions between the anode and cathode. Any suitable electrolyte material capable of conducting lithium ions between the electrodes, whether in solid, liquid, or gel form, can be used in the battery cell. For example, the electrolyte material can be a non-aqueous liquid electrolyte solution comprising a lithium salt dissolved in an organic solvent or a mixture of organic solvents.

[0147] Suitable lithium salts may have inert anions. Exemplary lithium salts that can be dissolved in an organic solvent or a mixture of organic solvents to form a non-aqueous liquid electrolyte solution include lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiBF2(C2O4))(LiODFB), lithium tetraphenylborate (LiB(C6H5)4), bis(oxalato) Lithium borate (LiB(C2O4)2) (LiBOB), lithium tetrafluorooxalatophosphate (LiPF4(C2O4)) (LiFOP), lithium nitrate (LiNO3), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonimide) (LiTFSI) (LiN(CF3SO2)2), lithium fluorosulfonyl imide (LiN(FSO2)2) (LiFSI), lithium fluoroalkyl phosphate (LiFAP) (Li3O4P) or a combination thereof.

[0148] Lithium salts can be dissolved in a variety of organic solvents, including, for example, alkyl carbonates, such as cyclic carbonates (e.g., ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC)), linear carbonates (e.g., dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC)), aliphatic carboxylates (e.g., methyl formate, methyl acetate, methyl propionate), γ-lactones (e.g., γ-butyrolactone, γ-valerolactone), fluorinated ethers (e.g., 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoroethyl) trifluoroethyl ether (TTE), bis(2,2,2-trifluoroethyl) ether (BTFE), tris(2,2,2-trifluoroethyl) orthoformate (TFEO), fluorinated esters (e.g. 2,2,2-trifluoroethyl ethyl carbonate (ETFEC), bis(2,2,2-trifluoroethyl) carbonate (BTC), 2,2,2-trifluoroethyl methyl carbonate (FEMC)), chain ethers (e.g. 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, ethoxymethoxyethane), cyclic ethers (e.g. tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane ring (DOL)), sulfur compounds (such as sulfolane), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIMTFSI), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIM-TFSI), N-propyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR13TFSI), 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR14TFSI), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMIM-FSI), 1-butyl-3-methyl The electrolyte material may include 1-butyl-1-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR13-FSI), 1-butyl-1-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR14-FSI), or a combination thereof. The electrolyte material may include one or more lithium salts in an amount of 0.5 mol / L (mol (M)) to 9.0 M or 0.5 M to 4.0 M. When the electrolyte material has a lithium concentration greater than 2 M or an ionic liquid, the electrolyte material may include fluoroethylene carbonate (FEC), hydrofluoroether (HFE), or a combination thereof.

[0149] Electrolyte materials, such as solid-state electrolytes, can act as both a conductor and separator for lithium ions, eliminating the need for a separate separator component. The solid-state electrolyte particles may include oxide particles, sulfide particles, metal-doped or asymmetrically substituted oxide particles, inactive oxide particles, nitride particles, hydride particles, halide particles, borate particles, or combinations thereof.

[0150] The oxide particles may include garnet ceramics, LISICON type oxides, NASICON type oxides, perovskite type ceramics or a combination thereof. For example, the garnet ceramic may be Li7La3Zr2O 12 、Li 6.2 Ga 0.3 La 2.95 Rb 0.05 Zr2O 12 、Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 、Li 6.25 Al 0.25 La3Zr2O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 , or a combination thereof. The LISICON type oxide may be Li 2+2x Zn 1-x GeO4 (where 0<x<1), Li 14 Zn(GeO4)4、Li 3+x (P 1-x Si x )O4 (where 0<x<1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1), or a combination thereof. NASICON-type oxides may be defined by LiMM(PO4)3, where M and M are independently Al, Ge, Ti, Sn, Hf, Zr, or La. For example, a NASICON-type oxide may be Li 1+ x Al x Ge 2-x (PO4)3(LAGP)(where 0≤x≤2), Li 1.4 Al 0.4 Ti 1.6 (PO4)3、Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3 or a combination thereof. The perovskite ceramic can be Li 3.3 La 0.53 TiO3、LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2xy Sr1x Ta y Zr 1y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25) or a combination thereof.

[0151] Metal-doped or aliovalent-substituted oxide particles can include, for example, Al (aluminum) or Nb (niobium)-doped Li7La3Zr2O 12 , Sb (antimony)-doped Li7La3Zr2O 12 , Ga (gallium)-doped Li7La3Zr2O 12 , Cr (chromium) V (vanadium)-substituted LiSn2P3O 12 , Al (aluminum)-substituted Li 1+x+y Al x Ti 2-x Si Y P 3-y O 12 (where 0 < x < 2 and 0 < y < 3) or a combination thereof.

[0152] Sulfide-based particles can include, for example, pseudo-binary sulfides, pseudo-tertiary sulfides, pseudo-quaternary sulfides or a combination thereof. Exemplary pseudo-binary sulfide systems include the Li2S-P2S5 system (e.g., Li3PS4, Li7P3S 11 and Li 9.6 P3S 12 ), the Li2S-SnS2 system (e.g., Li4SnS4), the Li2S-SiS2 system, the Li2S-GeS2 system, the Li2S-B2S3 system, the Li2S-Ga2S3 system, the Li2S-P2S3 system, the Li2S-Al2S3 system, Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S[[ID=5⑧]] 11.7 O 0.3 , the lithium thiogermanate Li6PS5X (where X is one of Cl, Br, and I). Exemplary pseudo-tertiary sulfide systems include the Li2O-Li2S-P2S5 system, the Li2S-P2S5-P2O5 system, the Li2S-P2S5-GeS2 system (e.g., Li 3.25 Ge 0.25 ]>P 0.75 S4 (thio-LISICON) and Li 10 GeP2S12 (LGPS)), Li2S-P2S5-LiX system (wherein X is one of F, Cl, Br and I) (such as Li6PS5Br, Li6PS5Cl, Li7P2S8I and Li4PS4I), Li2S-As2S5-SnS2 system (such as Li 3.833 Sn 0.833 As 0.166 S4), Li2S-P2S5-Al2S3 system, Li2S-LiX-SiS2 system (wherein X is one of F, Cl, Br and I), 0.4LiI·0.6Li4SnS4, and Li 11 Si2PS 12 Exemplary pseudo-quaternary sulfide systems include Li2O-Li2S-P2S5-P2O5 system, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0..3 、Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Ge 1.35 P 1.65 S 12 、Li 10.35 Si 1.35 P 1.65 S 12 、Li 9.81 Sn 0.81 P 2.1.9 S 12 、Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li 10 (Ge 0.5 Sne 0.5 )P2S 12 、Li 10 (Si 0.5 Sn 0.5 )P2S 12 、Li7P 2.9 Mn 0.1 S 10.7 I 0.3 、Li 3.833 Sn 0.833 As 0.166 S4, LiI-Li4SnS4, Li4SnS4 and Li 10.35 [Sn 0.27 Si 1.08 ]P 1.65 S12 .

[0153] Inactive oxide particles may include, for example, SiO2, Al2O3, TiO2, ZrO2, or a combination thereof; nitride particles may include, for example, Li3N, Li7PN4, LiSi2N3, or a combination thereof; hydride particles may include, for example, LiBH4, LiBH4-LiX (wherein X=Cl, Br, or I), LiNH2, Li2NH, LiBH4-LiNH2, Li3AlH6, or a combination thereof; halide particles may include, for example, LiI, Li3InCl6, Li2CdCl4, Li2MgCl4, LiCdI4, Li2ZnI4, Li3OCl, Li3YCl6, Li3YBr6, or a combination thereof; and borate particles may include, for example, Li2B4O7, Li2O-B2O3-P2O5, or a combination thereof.

[0154] The descriptions of cathode, anode, separator, and electrolyte materials presented herein are intended to be non-limiting examples. Many variations in the chemistry of each element may be employed in the context of the lithium-ion battery cells of the present disclosure.

[0155] Example

[0156] Comparative Example 1

[0157] A button cell is manufactured by mixing a slurry containing 60 to 98 weight percent (wt%) of a sulfur-carbon composite (containing 50 to 95 weight percent sulfur and 5 to 50 weight percent carbon), 1 to 20 weight percent of a binder, and 1 to 20 weight percent of a conductive material at a temperature of 1 mg / cm2. 2) The cathode was made by casting a load of 1000 nm onto an aluminum current collector. The anode was a lithium metal sheet, and an Entek nanoparticle fused polyethylene separator was used. Lithium bis(trifluoromethanesulfonyl)imide and tetraethylene glycol dimethyl ether (G4) (Li(G4)TFSI) were used as the electrolyte.

[0158] Example 1

[0159] A button cell was fabricated in which a slurry comprising 80 wt% (wt%) sulfur in 20 wt% Ketjen black, 70Li2S·25P2S5·5P2O5 solid electrolyte, SuperP conductive carbon, and hydrogenated nitrile rubber (HNBR) binder in a weight ratio of 60:20:10:10 was added to a slurry at 1 mg / cm2. 2 The cathode was made by casting a loading of ) on an aluminum current collector. The anode was a lithium metal sheet, and an Entek nanoparticle fused polyethylene separator was used. The electrolyte used was lithium bis(trifluoromethanesulfonyl)imide and tetraethylene glycol dimethyl ether (G4) (Li(G4)TFSI).

[0160] Figure 4 is a graph of voltage (volts (V)) versus specific capacity (milliampere-hours per gram (mAh / g)) for Comparative Example 1, and Figure 5 is a graph of voltage (V) versus specific capacity (mAh / g) for Example 1, where "1" represents cycle 1, "5" represents cycle 5, "10" represents cycle 10, and "20" represents cycle 20. The test included C / 20 in the first cycle and C / 10 in subsequent cycles. Figure 4 and Figure 5 It can be seen that higher specific capacity with good cycling stability can be achieved using the disclosed solid-state electrolyte. Figure 4 and Figure 5 In comparison, a higher plateau means lower impedance and lower overpotential.

[0161] Without wishing to be bound by any theory, it is believed that the disclosed solid electrolyte can improve lithium ion conductivity by providing more (one or more) lithium ion channels. The disclosed solid electrolyte can also provide reaction sites for S redox reaction.

[0162] The terms "a" and "an" do not indicate a quantitative limitation, but rather indicate the presence of at least one of the referenced items. The term "or" means "and / or" unless the context clearly indicates otherwise. References throughout this specification to "an aspect" mean that a particular element (e.g., feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein and may or may not be present in other aspects. In addition, it should be understood that the described elements can be combined in any suitable manner in each aspect.

[0163] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.

[0164] Unless otherwise specified herein, all test standards are the most current standards in effect as of the filing date of this application or, if priority is claimed, the filing date of the earliest priority application under which such test standards appeared.

[0165] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0166] Although the above disclosure has been described with reference to exemplary embodiments, it will be understood by those skilled in the art that various changes may be made and equivalents may be substituted for elements thereof without departing from the scope thereof. In addition, many modifications may be made to adapt a particular situation or material to the teachings of the present disclosure without departing from the essential scope thereof. Therefore, the present disclosure is not intended to be limited to the particular embodiments disclosed, but is intended to include all embodiments falling within its scope.

Claims

1. An electrochemical cell comprising: An electrode comprising: Sulfur conversion electroactive materials, and a solid electrolyte comprising sulfur oxide; Liquid electrolytes; Isolation parts; and Negative electrode.

2. The electrochemical cell according to claim 1, wherein: The solid electrolyte comprises 75Li2S-20P2S5-5P2O5; and The liquid electrolyte comprises Lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether (G3) (Li(G3)TFSI), or Bis(trifluoromethanesulfonyl)imide lithium salt and tetraethylene glycol dimethyl ether (G4) (Li(G4)TFSI), wherein the molar ratio of salt to solvent is 1:0.

8.

3. The electrochemical cell of claim 1, wherein the liquid electrolyte comprises a limited solvation liquid electrolyte.

4. The electrochemical cell of claim 3, wherein the separator comprises a porous polymer separator.

5. The electrochemical cell of claim 1, wherein the sulfur-conversion electroactive material comprises S, S8, Li2S8, Li2S6, Li2S4, Li2S2, Li2S, Fe2S, or a combination thereof.

6. The electrochemical cell of claim 1, wherein the solid electrolyte comprises yLi2S·(100-yx)P2S5·xP2O5, wherein y is 70 mol% to 80 mol%, and x is 0.5 mol% to 10 mol%.

7. The electrochemical cell of claim 1, wherein the solid electrolyte comprises Li 10 MP2S 12 , where M is Si, Ge or Sn; Li6PS5Cl; Li 3.25 Ge 0.25 P 0.75 S4; Li4GeS4; Li2S-P2S5 system; Li2S-SnS2 system; Li2S-SiS2 system; Li2S-GeS2 system; Li2S-B2S3 system; Li2S-Ga2S3 system; Li2S-P2S3 system; Li2S-Al2S3 system; Li 3.4 Si 0.4 P 0.6 S4; Li 10 GeP2S 11.7 O 0.3 ; Lithium argyrodite Li6PS5X, wherein X is Cl, Br or I; Li2O-Li2S-P2S5 system; Li2S-P2S5-P2O5 system; Li2S-P2S5-GeS2 system; Li2S-P2S5-LiX system, wherein X is F, Cl, Br or I; Li2S-As2S5-SnS2 system; Li2S-P2S5-Al2S3 system; Li2S-LiX-SiS2 system, wherein X is or F, Cl, Br and I; 0.4LiI·0.6Li4SnS4; Li 11 Si2PS 12 ;Li2O-Li2S-P2S5-P2O5 system; Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0..3 ;Li 9.6 P3S 12 ;Li7P3S 11 ;Li9P3S9O3;Li 10.35 Ge 1.35 P 1.65 S 12 ;Li 10.35 Si 1.35 P 1.65 S 12 ;Li 9.81 Sn 0.81 P 2.1.9 S 12 ;Li 10 (Si 0.5 Ge 0.5 )P2S 12 ;Li 10 (Ge 0.5 Sne 0.5 )P2S 12 ;Li 10 (Si 0.5 Sn 0.5 )P2S 12 ;Li7P 2.9 Mn 0.1 S 10.7 I 0.3 ;Li 3.833 Sn 0.833 As 0.166 S4; LiI-Li4SnS4; Li4SnS4; Li 10.35 [Sn 0.27 Si 1.08 ]P 1.65 S 12 ; or a combination thereof.

8. The electrochemical cell of claim 1, wherein the liquid electrolyte comprises a solvated ionic liquid, the solvated ionic liquid comprising a lithium salt of bis(trifluoromethanesulfonyl)imide and diglyme (G2) (Li(G2)TFSI), a lithium salt of bis(trifluoromethanesulfonyl)imide and triglyme (G3) (Li(G3)TFSI), a lithium salt of bis(trifluoromethanesulfonyl)imide and tetraglyme (G4) (Li(G4)TFSI), a lithium salt of bis(fluorosulfonyl)imide and diglyme (G2) (Li(G2)FSI), a lithium salt of bis(fluorosulfonyl)imide and triglyme (G3) (Li(G3)FSI), a lithium salt of bis(fluorosulfonyl)imide and tetraglyme (G4) (Li(G4) FSI), bis(pentafluoroethanesulfonyl)imide lithium salt and diethylene glycol dimethyl ether (G2) ([Li(G2)]BETI), bis(pentafluoroethanesulfonyl)imide lithium salt and triethylene glycol dimethyl ether (G3) ([Li(G3)]BETI), bis(pentafluoroethanesulfonyl)imide lithium salt and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]BETI), cyano(trifluoromethanesulfonyl)imide lithium salt and diethylene glycol dimethyl ether (G2) ([Li(G2)]CTFSI), cyano(trifluoromethanesulfonyl)imide lithium salt and triethylene glycol dimethyl ether (G3) ([Li(G3)]CTFSI), cyano(trifluoromethanesulfonyl)imide lithium salt and tetraethylene glycol dimethyl ether (G4) ([Li( G4)]CTFSI), lithium perchlorate and diethylene glycol dimethyl ether (G2) ([Li(G2)]ClO4), lithium perchlorate and triethylene glycol dimethyl ether (G3) ([Li(G3)]ClO4), lithium perchlorate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]ClO4), lithium tetrafluoroborate and diethylene glycol dimethyl ether (G2) ([Li(G2)]BF4), lithium tetrafluoroborate and triethylene glycol dimethyl ether (G3) ([Li(G3)]BF4), lithium tetrafluoroborate and tetraethylene glycol dimethyl ether (G4) ([Li(G4)]BF4), lithium nitrate and diethylene glycol dimethyl ether (G2) ([Li(G2)]NO3), lithium nitrate and triethylene glycol dimethyl ether (G 3)([Li(G3)]NO3), lithium nitrate and tetraethylene glycol dimethyl ether (G4)([Li(G4)]NO3), lithium trifluoromethanesulfonate and diethylene glycol dimethyl ether (G2)([Li(G2)]OTf), lithium trifluoromethanesulfonate and triethylene glycol dimethyl ether (G3)([Li(G3)]OTf), lithium trifluoromethanesulfonate and tetraethylene glycol dimethyl ether (G4)([Li(G4)]OTf), lithium trifluoroacetate and diethylene glycol dimethyl ether (G2)([Li(G2)]TFA), lithium trifluoroacetate and triethylene glycol dimethyl ether (G3)([Li(G3)]TFA), lithium trifluoroacetate and tetraethylene glycol dimethyl ether (G4)([Li(G4)]TFA), or a combination thereof.

9. The electrochemical cell of claim 1, wherein the liquid electrolyte comprises an ionic liquid electrolyte comprising 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIM-TFSI), N-propyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR13TFSI), 1-butyl-1-methyl The invention can be selected from the group consisting of 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMIM-FSI), 1-butyl-3-methylimidazolium bis(fluorosulfonyl)imide (BMIM-FSI), N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR13-FSI), 1-butyl-1-methylpyrrolidinium bis(fluorosulfonyl)imide (PYR14-FSI), or a combination thereof.

10. The electrochemical cell of claim 1, wherein the liquid electrolyte comprises: Organic solvents, including ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, methyl propionate, γ-butyrolactone, γ-valerolactone, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoroethyl) carbonate (ETFEC), bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,3,3,3-hexafluoropropyl- 2,2,2-trifluoroethyl ether, methyl 3,3,3-trifluoropropionate or ethyl trifluoroacetate, tris(2,2,2-trifluoroethyl)orthoformate (TFEO), bis(2,2,2-trifluoroethyl)carbonate (BTC), 2,2,2-trifluoroethylmethyl carbonate (FEMC), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, ethoxymethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane (DOL), sulfolane, diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether (G3), tetraethylene glycol dimethyl ether (G4), or a combination thereof; and Lithium salts, including lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiBF2(C2O4))(LiODFB), lithium tetraphenylborate (LiB(C6H5)4), lithium bis(oxalato)borate (LiB(C2O4)2)(L iBOB), lithium tetrafluorooxalato phosphate (LiPF4(C2O4))(LiFOP), lithium nitrate (LiNO3), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI)(LiN(CF3SO2)2), lithium fluorosulfonyl imide (LiN(FSO2)2)(LiFSI), lithium fluoroalkyl phosphate (LiFAP)(Li3O4P), or a combination thereof.

11. The electrochemical cell of claim 1, wherein the sulfur-converting electroactive material comprises a sulfur-carbon composite, a Li2S-C composite, a sulfurized polyacrylonitrile, or a combination thereof.

12. The electrochemical cell of claim 1, wherein the electrode further comprises a conductive material comprising carbon black, graphite, acetylene black, carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powder, liquid metal, conductive polymer, or a combination thereof.

13. The electrochemical cell of claim 1 , wherein the electrode further comprises a binder, the binder comprising styrene-butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), polytetrafluoroethylene (PTFE), poly(tetrafluoroethylene-co-perfluoro(3-oxa-4-pentenesulfonic acid)) lithium salt, sodium carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, ethylene propylene diene monomer (EPDM), or a combination thereof.

14. The electrochemical cell of claim 13, wherein the electrode comprises, based on the total weight of the electrode: 40 to 70 wt % of said sulfur-converting electroactive material; 5 to 30 wt % of a solid electrolyte; 0.1 to 20 wt % of said binder; and 0.1 to 30 wt % of the conductive material.

15. The electrochemical cell of claim 1, wherein the negative electrode comprises lithium, graphite, graphene, hard carbon, soft carbon, carbon nanotubes, silicon, a silicon-containing alloy, a tin-containing alloy, or a combination thereof.

16. An electrochemical cell comprising: An electrode comprising Sulfur conversion electroactive materials, and Oxide solid electrolyte; Liquid electrolytes; Isolation parts; and Negative electrode.

17. The electrochemical cell of claim 16, wherein the liquid electrolyte comprises a limited solvation liquid electrolyte comprising a solvated ionic liquid.

18. The electrochemical cell of claim 16, wherein: The oxide solid electrolyte comprises Li 1+x Al x Ge 2-x (PO4)3(LAGP)(where 0≤x≤2), Li7La3Zr2O 12 (LLZO), or Li 1+x Al x Ti 2-x (PO4)3(LATP) (where 0≤x≤2); and The liquid electrolyte comprises Lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether (G3) (Li(G3)TFSI), or Bis(trifluoromethanesulfonyl)imide lithium salt and tetraethylene glycol dimethyl ether (G4) (Li(G4)TFSI), wherein the molar ratio of salt to solvent is 1:0.

8.

19. An electrochemical cell comprising: An electrode comprising Sulfur conversion electroactive materials, and a solid electrolyte comprising a sulfide; Liquid electrolytes; Isolation parts; and Negative electrode.

20. The electrochemical cell of claim 19, wherein the liquid electrolyte comprises a limited solvation liquid electrolyte comprising a solvated ionic liquid.